Safety of chronic high-dose calcium channel blockers exposure in children with pulmonary arterial hypertension - Wu, Yan; Peng, Fu-Hua; Gao, Xin; Yan, Xin-Xin; Zhang, FengWen; Tan, Jiang-Shan; Hu, Song; Hua, Lu (Frontiers in Cardiovascular Medicine, 2022)
Background Chronic calcium channel blockers (CCBs) are indicated in children with idiopathic/heritable pulmonary arterial hypertension (IPAH/HPAH) and positive response to acute vasodilator challenge. However, minimal safety data are available on the long-term high-dose exposure to CCBs in this population. Methods Patients aged 3 months to 18 years who were diagnosed with IPAH/HPAH and treated with CCB in the past 15 years were retrospectively reviewed. The maximum tolerated dose and the long-term safety of high-dose CCBs on the cardiovascular and noncardiovascular systems were assessed. Results Thirty-two eligible children were enrolled in the study, with a median age of 9 (6–11) years old. Thirty-one patients were treated with diltiazem after diagnosis. The median maximum tolerated dose was 12.9 (9.8–16.8) mg/kg/day. Children younger than 7 years used higher doses than children in the older age group, 16.4 (10.5–28.5) mg/kg/day vs. 12.7 (6.6–14.4) mg/kg/day, P < 0.05. Patients were followed up for a median period of 6.2 (2.6–10.8) years. One patient died from a traffic accident, and others showed a stable or improved WHO functional class status. Thirteen (40.6%) and 10 (31.3%) patients developed arrhythmias and hypotension. Nine (28.1%) patients had sinus bradycardia, five (21.9%) had first-degree or second-degree type II atrial-ventricular blocks, and two (6.3%) had second-degree type II atrial-ventricular blocks. Most of these arrhythmias were transient and relieved after CCB dose adjustment. The most reported noncardiovascular adverse effect was gingival hyperplasia (13, 40.6%), accompanied by different degrees of dental dysplasia. No liver or kidney dysfunction was reported. Conclusion Diltiazem was used in a very high dose for eligible children with IPAH/HPAH. The toxicity of long-term CCB use on the cardiovascular system is mild and controllable. Clinicians should also monitor the noncardiovascular adverse effects associated with drug therapy.